THE EFFECTIVENESS OF A RESEARCH-BASED TEACHING APPROACH IN POSTGRADUATE PROPERTY SUBJECTS - Hassan Gholipour Fereidouni (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The purpose of this study is to evaluate the effectiveness of a research-based teaching approach in postgraduate property subjects over the period 2020–2025. The subjects include a mix of domestic and international students, predominantly from Asian countries. The research-based teaching intervention was implemented across two postgraduate property subjects and embedded into both content delivery and assessment design. Using longitudinal subject evaluation data, learning analytics, and student performance outcomes, the study examines changes in student satisfaction, teaching effectiveness, and academic success over time. The findings indicate that overall student satisfaction with both the subjects and the instructor has increased significantly over the five-year period, alongside a notable improvement in student pass rates. The effectiveness of this approach is attributed to several mechanisms, including the integration of contemporary research into teaching materials, the use of real-world datasets and policy-relevant case studies, research-oriented assessments, explicit instruction in research methods and academic writing, and structured formative feedback. In addition, students were actively engaged in research discussions and encouraged to critically evaluate academic literature, fostering deeper learning and analytical skills. The results suggest that a research-based teaching approach can enhance student engagement, learning outcomes, and academic confidence in postgraduate property education, particularly in culturally diverse cohorts. The study contributes to the scholarship of teaching and learning by providing empirical evidence on how research-led pedagogy can be effectively operationalised in postgraduate business and property disciplines.